The Association of Positive or Negative Religious Coping Methods With Psychological Distress and Quality of Life Among Parents of Infants With Congenital Heart Disease - Liu, Jian-Feng; Xie, Wen-Peng; Lin, Wen-Hao; Cao, Hua; Chen, Qiang (Frontiers in Pediatrics, 2021)
Objective: The purpose of this study was to evaluate whether positive and negative religious coping methods were associated with psychological distress and quality of life in parents of infants with congenital heart disease (CHD). Methods: This descriptive, cross-sectional study was conducted at a provincial hospital in Fujian, China. Clinical data from 115 parents of infants with CHD were collected. Chinese Sociodemographic Forms, Brief RCOPE, Beck Depression Interview (BDI), and the Short Form Health Survey (SF-36) were used in this study. Results: The sex of caregivers in infants with CHD was an independent predictor of BDI scores. The positive religious coping score and the negative religious coping score were both independent predictors of the BDI score (β=-5.365, P=0.006 and β=4.812, p=0.017). The correlation between the quality-of-life scores and positive or negative religious coping scores indicated that positive religious coping scores were significantly positively correlated with Vitality, Social Functioning, and Mental Health scores. There was a significant negative correlation between negative religious coping scores and mental health scores. Conclusions: Positive or negative religious coping methods may be associated with psychological distress and quality of life among parents of infants with CHD. It is suggested that more attention should be devoted to the influence of religious coping methods on parents of infants with CHD, and the use of religious resources should be encouraged.